Public acceptance toward naturalistic landscape in Kuala Lumpur's urban park, Malaysia - Mohd Ariffin, Nur Diyana (2023)
Kuala Lumpur has signalled a modernised and progressive metropolitan city with massive changes in physical infrastructure and the city's environment including the urban parks. Thus, there is a need to develop more appropriate measures for managing these landscapes sustainably. Implementing a naturalistic landscape style in tropical urban parks may represent a different appearance. it would create different public reactions compared to the current landscape style. Therefore, this study aims to investigate the public acceptance of landscape style in Kuala Lumpur's urban parks and changing it to a more naturalistic landscape style. Objectives for this study are 1) to access public acceptance for landscape style in an urban park and changes towards naturalistic landscape style, 2) to analyse the factor that influences public acceptance for naturalistic landscape style in an urban park, and 3) to make recommendations of suitable naturalistic landscape style in Kuala Lumpur’s urban park according to public acceptance. A questionnaire survey was conducted to collect the data of three selected urban parks in Kuala Lumpur, which are Perdana Botanical Garden (PBG), Ampang Hilir Park (AHP), and Bukit Kiara Federal Park (BKFP) have been polled for their acceptance regards familiarity with nature, usability of park, visual acceptance, level of agreement towards naturalistic landscape and demographic. The result found that the public generally accepts the existing and naturalistic landscapes under certain conditions, such as the type of area it is located and their function, as the majority of them come to the park for leisure with family and friends. The public is willing to accept such a landscape style with some considerations. This research's significant outcome will help determine the suitable appearance of the naturalistic landscape style for implementation based on public acceptance.